ANALYSIS OF TROPOSPHERIC OZONE CONCENTRATIONS AND METEOROLOGICAL FACTORS IN DKI JAKARTA IN 2018-2020 - Zul Hikma, Alifah
Ozone is a common secondary pollutant in urban areas. The analysis of ozone concentrations temporally this time is intended to find out the picture of ambient air ozone concentrations in urban areas, especially DKI Jakarta in 2018-2020. The study's goal was to determine diurnal variations in ozone, an average ozone concentration of 1 hour and 8 hours to compare with national quality standards, as well as factors that influence fluctuations in ambient air ozone concentrations. The data used comes from the results of continuous monitoring in 5 monitoring locations spread across every administrative city in DKI Jakarta. The pattern of diurnal variation shows that the peak hours